Board of Directors and Commissioners Fulfillment of Commitments in Enterprise Risk Management Implementation and Supervision in Indonesian Coal Mining Company (Case Study of PT XYZ) - Dwi Ayuningrat Subagiono Soepeno; Maria Widyarini; Achmad Faisal (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The goal of this study is to learn about, analyze, and describe two things, namely the Board of Directors and board commissioners' commitment to implementing and monitoring ERM in order to protect and create value for the company and the Management's perspectives on ERM's ability to protect and create value for the company. Data were gathered through structured interviews and a documentation study. The findings showed that the boards had followed through on their promise to implement and supervise ERM. This study identifies areas for improvement in integrating ERM into strategy development, risk culture, common risk language, risk management tools, and the role of the ERM function. Although numerous studies have looked at the influence of ERM implementation on firm value, this study seeks to fill a knowledge gap on the Boards' commitment to implementing and monitoring ERM to protect and build value for the company. Effective ERM implementation necessitates the involvement of the boards of directors.Keywords: Enterprise Risk Management (ERM), Board’s Commitment, and Protect and Create Value for Company. AbstrakTujuan dari penelitian ini adalah untuk mempelajari, menganalisis, dan mendeskripsikan dua hal, yaitu komitmen Direksi dan dewan komisaris dalam menerapkan dan memantau ERM dalam rangka melindungi dan menciptakan nilai bagi perusahaan dan perspektif Manajemen terhadap kemampuan ERM untuk melindungi dan menciptakan nilai bagi perusahaan. Pengumpulan data dilakukan melalui wawancara terstruktur dan studi dokumentasi. Temuan menunjukkan bahwa dewan telah menepati janji mereka untuk menerapkan dan mengawasi ERM. Studi ini mengidentifikasi area untuk perbaikan dalam mengintegrasikan ERM ke dalam pengembangan strategi, budaya risiko, bahasa risiko umum, alat manajemen risiko, dan peran fungsi ERM. Meskipun banyak penelitian telah melihat pengaruh penerapan ERM pada nilai perusahaan, penelitian ini berusaha untuk mengisi kesenjangan pengetahuan tentang komitmen Dewan untuk menerapkan dan memantau ERM untuk melindungi dan membangun nilai bagi perusahaan. Implementasi ERM yang efektif memerlukan keterlibatan dewan direksi.Kata kunci: Enterprise Risk Management (ERM); Komitmen Dewan; Protect and Create Value for Company.